He's Max-Min Approach to a Nonlinear Oscillator with Discontinuous Terms - Hui-Li Zhang; Fang Xie (Abstract and Applied Analysis)
Recently, the max-min approach was systematically studied in the review article (Ji-Huan, 2012). This paper concludes that He's max-min approach is also a very much effective method for nonlinear oscillators with discontinuous terms.